Constructivism and Teaching-Learning Process in Christian School: Case Study in a Christian School in Tangerang, Indonesia - Tirza, Juliana (International Journal of Psychosocial Rehabilitation, 2020)
Students are very excited and interested in the creative learning process. Students’ interest in learning will increase if they study in a conducive environment, well-prepared learning resources, clear class rules and potential and enthusiastic teachers. Not a few students will return home with a disappointing story, if the learning process at school does not go well. It is not impossible if sad or annoying stories also occur in classes in Christian schools.Good memorable learning will be difficult to achieve if students are always asked by the teacher to memorize, repeat the subject matter, make presentations, plus attend additional classes after school hours. Learning portraits like this make learning tiring and pressing for students. If so, then the work ethic and professionalism of teachers will be questioned by school leaders, parents of students.One solution to an effective learning process is to rethink the approach used in the teaching and learning process. The world of philosophy offers several streams of educational philosophy that are often used as a basis and approach in the teaching and learning process. In this paper, one philosophy will be discussed, which is constructivism and its approach in relation to the teaching and learning process in Christian schools. Therefore, the issues are what is the view of constructivism towards education? Can constructivism be applied in learning in Christian schools? Christian school’s classrooms cannot be the only location for knowledge transfer. Teachers must be able to balance the application of one-way learning and constructivism in their classrooms. Teachers cannot think that students are like empty vessels that need to be filled continuously, as the tabula rasa concept views humans. Student participation in class is also important to be concerned about, so students feel not pressured or too restricted when learning.